2016
DOI: 10.1016/j.cels.2016.09.002
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Cell Transcriptome Atlas of the Human Pancreas

Abstract: SummaryTo understand organ function, it is important to have an inventory of its cell types and of their corresponding marker genes. This is a particularly challenging task for human tissues like the pancreas, because reliable markers are limited. Hence, transcriptome-wide studies are typically done on pooled islets of Langerhans, obscuring contributions from rare cell types and of potential subpopulations. To overcome this challenge, we developed an automated platform that uses FACS, robotics, and the CEL-Seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
1,240
5
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,128 publications
(1,275 citation statements)
references
References 59 publications
28
1,240
5
2
Order By: Relevance
“…These data confirm the striking differences between species as previously reported for the human and murine alpha- and beta-enriched genes [12, 21]. Importantly, many of the conserved alpha- and beta-specific genes identified in the present study were also recently highlighted as enriched in these endocrine cell types in several single cell RNA-seq studies [1921] (Additional file 14: Table S8 (beta cells) and Additional file 15: Table S9 (alpha cells) for comparison).
Fig. 7Identification of genes with conserved enriched expression in alpha and beta cells.
…”
Section: Resultssupporting
confidence: 92%
“…These data confirm the striking differences between species as previously reported for the human and murine alpha- and beta-enriched genes [12, 21]. Importantly, many of the conserved alpha- and beta-specific genes identified in the present study were also recently highlighted as enriched in these endocrine cell types in several single cell RNA-seq studies [1921] (Additional file 14: Table S8 (beta cells) and Additional file 15: Table S9 (alpha cells) for comparison).
Fig. 7Identification of genes with conserved enriched expression in alpha and beta cells.
…”
Section: Resultssupporting
confidence: 92%
“…Three research groups have described heterogeneity in the beta cell population with particular gene signatures driving such differences (Baron et al, 2016; Muraro et al, 2016; Segerstolpe et al, 2016). However, Xin et al (2016b) were not able to detect such diverse cell types.…”
Section: Molecular Heterogeneitymentioning
confidence: 99%
“…For example, these studies revealed that delta cells uniquely express appetite-suppressing leptin ( LEPR ) and appetite-stimulating ghrelin ( GHSR ) hormone receptors [75,79,80], implicating them as the integrators and regulators of these pathways in the islet. GHSR functionality has been demonstrated in both human and mouse delta cells [70].…”
Section: Deconstructing Pancreatic Islet Cellular/functional Heterogementioning
confidence: 99%
“…GHSR functionality has been demonstrated in both human and mouse delta cells [70]. LEPR expression is unique to human delta cells, suggesting that these cells may uniquely mediate the leptin response in human islets [70,75,76,79,80] (Figure 2). Expression of genes associated with congenital hyperinsulinemia (CHI) ( UCP2, HADH ) in delta cells further implicates this cell type in the molecular genetics of CHI [75].…”
Section: Deconstructing Pancreatic Islet Cellular/functional Heterogementioning
confidence: 99%
See 1 more Smart Citation